Dissimilar populations of EpСam-positive cells in ascitic fluid of ovarian cancer patients: a relationship with the degree of carcinomatosis - E. V. Kaigorodova; M. O. Ochirov; S. V. Molchanov; R. R. Rogachev; D. A. Dyakov; A. L. Chernyshova; O. V. Shpileva; O. I. Kovalev; S. V. Vtorushin (Бюллетень сибирской медицины, 2021)
Background. Peritoneal carcinomatosis (PC) is one of the most unfavorable factors of ovarian cancer progression. It is often accompanied by accumulation of fluid in the abdominal cavity, which is called ascites. However, prognostic factors associated with malignant ascites are not well understood.The aim of this study was to evaluate dissimilar populations of EpCAM-positive cells in ascitic fluid and their relationship with the presence of invasive peritoneal implants and the prevalence of carcinomatosis on the Predictive Index Value (PIV) scale in ovarian cancer patients.Materials and methods. The prospective study included 22 patients aged 36–76 years with newly diagnosed FIGO stage Ic–IV ovarian cancer, who were admitted for treatment to Cancer Research Institute of Tomsk NRMC. The study material included EDTA-stabilized ascitic fluid sampled during laparoscopy. Various populations of ascites tumor cells were identified by laser multicolor flow cytometry. The degree of carcinomatosis was determined according to the PIV scale.Results. The study identified twelve populations of EpCAM-positive cells in the ascitic fluid of ovarian cancer patients. Epcam+CD45-CD44-CD24+CD133-Ncadherin+ cells (r = 0.58; p = 0.004) and atypical (hybrid) EpCam+CD45+CD44+CD24+/-CD133+/-Ncadherin+/- cells (r = = 0.51; р = 0.01) had a positive correlation with the PIV index.Conclusion. The obtained results show a high degree of heterogeneity of tumor cells in the ascitic fluid of ovarian cancer patients. Identified atypical (hybrid) forms of EpCam-positive cells are of great interest for cell biology and require further investigation.